2018
DOI: 10.1002/path.5141
|View full text |Cite
|
Sign up to set email alerts
|

VEGF receptor‐2/neuropilin 1 trans‐complex formation between endothelial and tumor cells is an independent predictor of pancreatic cancer survival

Abstract: Unstable and dysfunctional tumor vasculature promotes cancer progression and spread. Signal transduction by the pro‐angiogenic vascular endothelial growth factor (VEGF) receptor‐2 (VEGFR2) is modulated by VEGFA‐dependent complex formation with neuropilin 1 (NRP1). NRP1 expressed on tumor cells can form VEGFR2/NRP1 trans‐complexes between tumor cells and endothelial cells which arrests VEGFR2 on the endothelial surface, thus interfering with productive VEGFR2 signaling. In mouse fibrosarcoma, VEGFR2/NRP1 trans‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…However, the compartment-specific expression of NRP1, and the ability to form VEGFR2/NRP1 complexes in trans were not explored in these studies. Findings from our previous work, supported by the present study, suggest that the NRP1 expression pattern, not only the overall expression levels, is of critical importance for tumor progression and patient prognosis [22]. Thus, tumor cell expression of NRP1 (see supplementary material, Figure S4A,B) and more importantly, perivascular tumor cell expression ( Figure 3A,B), correlated with improved outcome in two independent RCC cohorts.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, the compartment-specific expression of NRP1, and the ability to form VEGFR2/NRP1 complexes in trans were not explored in these studies. Findings from our previous work, supported by the present study, suggest that the NRP1 expression pattern, not only the overall expression levels, is of critical importance for tumor progression and patient prognosis [22]. Thus, tumor cell expression of NRP1 (see supplementary material, Figure S4A,B) and more importantly, perivascular tumor cell expression ( Figure 3A,B), correlated with improved outcome in two independent RCC cohorts.…”
Section: Discussionsupporting
confidence: 83%
“…The pattern of VEGFR2 and NRP1 expression in RCC, that is, VEGFR2 in the endothelial cells and NRP1 in both endothelial and tumor cells, indicated that VEGFR2/NRP1 complexes could form both in trans and cis configurations. To identify such complexes in human RCC tissue, in situ PLA was performed on consecutive sections with antibodies against VEGFR2 and NRP1, as described previously (Figure C) . Patient biopsies were scored positive or negative for VEGFR2/NRP1 complexes in trans and cis configurations (see material and methods for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…human cancers have been confirmed with animal studies showing that exacerbated angiogenesis and a poor prognosis is correlated with NRP1 expression (Ellis, 2006). Only in pancreatic cancers, a high expression of NRP1 correlates with reduced vascularized areas, decreased tumor growth, and improved survival (Morin et al, 2018).…”
Section: Functions Of Neuropilins In Cancermentioning
confidence: 85%
“…A previously described tissue microarray was used for the tissue studies . The tissue microarray has core areas of 1 mm in diameter selected by an experienced pathologist (WW).…”
Section: Methodsmentioning
confidence: 99%